Study on Mechanical Properties and Energy Consumption of Fissured Sandstone with Different Dip Angles under Impact Load. (11th May 2022) - Ping, Qi; Wang, Shuo; Wu, Yulin; Sun, Shijia; Shen, Kaifan; Wang, Chen; Gao, Qi; Fang, Chenglong
Abstract : To study the dynamic mechanical properties and energy consumption of fissured sandstone with different dip angles under impact load, impact compression tests were conducted on seven groups of and intact and fractured sandstone specimens with different dip angles using the split Hopkinson pressure bar (SHPB) device with 0.3 MPa air pressure. The influence of dip fissures on the crushing shape, dynamic compressive strength, dynamic elastic modulus, dynamic peak strain, dynamic average strain rate, dynamic stress-strain curve, and energy consumption of rock specimens was systematically analyzed. The results show that the 45° fissure angle is the best fragile angle according to the failure mode and dynamic compressive strength of the specimen and that difference in specimen failure modes specimens is attributed to the existence of fractures with different dip angles. The dynamic elastic modulus reaches the minimum when the fissure angle is 45° and the maximum when the fissure angle is 90°. The dynamic peak strain is the lowest and minimal influence of fissure angle on the average strain rate of the specimen is presented when the fissure angle is 45°. From the stress-strain curves, the two specimen ends are most vulnerable to the relative sliding and dislocation of the lateral fissure angle during impact compression when the fissure angle is 45°. With stable incident energy in the test, a prominent relationship exists between the reflected energy, transmission energy, and energy consumption and the fissure angles. In addition, the fissure angle exhibits a prominent influence on reflected energy and the energy consumption of the specimen when the fissure angle ranges from 45° to 60°.